2020
DOI: 10.1039/c9cc09613b
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Doping improves the performance of Ru-based electrocatalysts for the acidic oxygen evolution reaction

Abstract: Magnesium doped RuO2 exhibits excellent acidic oxygen evolution reaction performance with an overpotential of 228 mV at 10 mA cm−2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A solvothermal reaction is a facile synthesis strategy for introducing metal ions into the precursor, which is further converted to multimetallic, compound-doped carbons through a post-annealing process. [26,[110][111][112][113][114][115] Li et al reported a novel dispersing-etching-holing (DEH) approach to fabricate the 3D open nanonet-cage electrocatalyst (Figure 7Ba,b). [114] The operando XAS results confirmed that ZnO could be etched in situ during the HER process, while the provided RuIr alloy acted as the active sites (Figure 7Bc,d).…”
Section: Metal-compound-doped Carbon Electrocatalystsmentioning
confidence: 99%
“…A solvothermal reaction is a facile synthesis strategy for introducing metal ions into the precursor, which is further converted to multimetallic, compound-doped carbons through a post-annealing process. [26,[110][111][112][113][114][115] Li et al reported a novel dispersing-etching-holing (DEH) approach to fabricate the 3D open nanonet-cage electrocatalyst (Figure 7Ba,b). [114] The operando XAS results confirmed that ZnO could be etched in situ during the HER process, while the provided RuIr alloy acted as the active sites (Figure 7Bc,d).…”
Section: Metal-compound-doped Carbon Electrocatalystsmentioning
confidence: 99%
“…The high overpotential of the OER reaction is the most important factor affecting the efficiency of water electrolysis. [11][12][13][14][15][16][17][18][19][20] Up to now, despite a lot of research, RuO 2 is still considered to be the most active electrocatalyst for OER. However, its overpotential is still not low enough, and it has disadvantages such as poor stability and high price, which still needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, MOFs and MOF‐derivatives have attracted extensive research interests for versatile properties in many fields (such as adsorption and catalysis) because of their tunable porosities, open channels, versatile functionalities and superhigh specific surface areas [9a,13] . In some synthesis process of electrocatalysts, like annealing, MOFs are usually used as precursors to obtained alloys, [14] doped oxides, [12a] heterojunctions, [15] metal‐nitrogen‐carbon system [9a,16] and other carbon based catalyst [17] . In some previous studies, the catalyst containing zinc element showed potential catalytic performance toward OER [18] .…”
Section: Methodsmentioning
confidence: 99%